Rainbow years: conflict to contentment - Gopal, Madabhushi Madan (Gurugram Garuda Publication, 2022)
Beginning 1960s, Marxist ideology was the flavour of the youth. Convinced about the revolution that must come, three friends$1 (BRajen, Suri and Mallana$1 (Bset out charting their paths through the Left-Wing organisations and movement. As decades pass by, the strategies fail, the ideologies get diluted, connect with the masses is lost, they allow foreign intervention. Of course, the state played its own games. When they meet again after the momentous decades, there is no scope to be judgemental; they must accept the vicissitudes of life. The novel is the journey of a generation that dreamt of a revolution, the dream shattered by the calming realisation that being of service to the common people$1 (Bwith a sense of non-doership$1 (Bwas the only dream worth pursuing.s
Keywords: English Fiction; IAS as an author